Given: $$p(x) = x^4 - 5773x^3 - 46464x^2 - 5773x + 46$$

What is the sum of all arctan of all the roots of $p(x)$?


Let $p_1,p_2,p_3,p_4$ be the roots of $p(x)=0$

So, we need $\arctan p_1+\arctan p_2+\arctan p_3+\arctan p_4$

Using Vieta's Formulae,

$\sum p_i=p_1+p_2+p_3+p_4=\frac{5773}1$

$\sum p_ip_j=p_1p_2+p_1p_3+p_1p_4+p_2p_3+p_2p_4+p_3p_4=\frac{46464}1$

$\sum p_ip_jp_k=p_1p_2p_3+p_1p_2p_4+p_1p_3p_4+p_2p_3p_4=\frac{5773}1$


We know, $$\tan(A+B+C+D)$$

$$=\frac{\tan A+\tan B+\tan C+\tan D -(\tan A\tan B\tan C+\tan A\tan B\tan D+\tan A\tan C\tan D+\tan B\tan C\tan D)}{1- (\tan A\tan B+\tan A\tan C+\tan A\tan D+\tan B\tan C+\tan B\tan D+\tan C\tan D)+ \tan A\tan B\tan C\tan D}$$

If we put $p_1=\tan A,p_2=\tan B$ etc.,

$$\tan(A+B+C+D)=\frac{p_1+p_2+p_3+p_4 -(p_1p_2p_3+p_1p_2p_4+p_1p_3p_4+p_2p_3p_4)}{1- (p_1p_2+p_1p_3+p_1p_4+p_2p_3+p_2p_4+p_3p_4)+ p_1p_2p_3p_4}$$


So, $\tan(A+B+C+D)=0\implies A+B+C+D=\arctan (0)$

$\implies \arctan p_1+\arctan p_2+\arctan p_3+\arctan p_4=\arctan (0)$

The general value of $\arctan (0)$ is $n\pi$ where $n$ is any integer, the special value being $0$(putting $n=0$)

| cite | improve this answer | |
  • 1
    $\begingroup$ i was really hoping for something a little more elementary, since I really can't understand any of these deductions (im senior high school student). I was hoping these olympiad questions were within reach. Thanks anyways! $\endgroup$ – Or Cyngiser Dec 24 '12 at 19:57
  • 2
    $\begingroup$ That's pretty much the simplest way to do it, really. $\endgroup$ – Joe Z. Dec 24 '12 at 20:08
  • $\begingroup$ @JoeZeng, thanks. Wish there is a simpler way for Or Cyngiser. $\endgroup$ – lab bhattacharjee Dec 24 '12 at 20:12
  • $\begingroup$ I think I see where the confusion is. You haven't expressed your answer in the form of arctans. Are A, B, C, and D the arctans of the solutions to p(x)? $\endgroup$ – Joe Z. Dec 24 '12 at 20:19
  • $\begingroup$ @Joe Zeng: Yes the notation could be improved a bit. It is also not clear what $\sum \tan A$ and $\sum \tan A \tan B$ should stand for... (sum over what, if $A$ is the arctan of a solution...) $\endgroup$ – Fabian Dec 24 '12 at 20:28

Nothing additional, but for the OP a more elementary approach.

$(x-a_1)(x-a_2)(x-a_3)(x-a_4) = x^4 - c_1x^3 + c_2x^2 - c_3x + a_1a_2a_3a_4.$ Where $c_1 = \Sigma a_i$, $c_2 = \Sigma_{i<j}a_ia_j$ and $c_3 = \Sigma_{i <j < k}a_ia_ja_k$. Let $t_i=\tan^{-1}a_i.$ You want to compute $\Sigma t_i.$ Here, the trick is knowing the $\tan(x+y)$ expansion $$\tan(x+y) = \frac{\tan x + \tan y}{1- \tan x \tan y}.$$
Apply twice for $x=t_1+t_2$ and $y=t_3+t_4$. $$\tan(t_1+t_2+t_3+t_4) = \frac{\tan(t_1+t_2) + \tan(t_3+t_4)}{1+\tan(t_1+t_2)\tan(t_3+t_4)}=\frac{\frac{a_1 + a_2}{1- a_1a_2}+\frac{a_3 + a_4}{1- a_3a_4}}{1-\frac{a_1 + a_2}{1- a_1a_2}\frac{a_3 + a_4}{1- a_3a_4}} = \frac{(a_1+a_2)(1-a_3a_4)+(a_3+a_4)(1-a_1a_2)}{(1-a_1a_2)(1-a_3a_4)-(a_1+a_2)(a_3+a_4)}=\frac{c_1-c_3}{1+c_4-c_2}.$$ For this polynomial $c_1=c_3$, thefore $\tan\Sigma t_i =0,$ so is $\Sigma t_i =0$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.